Analysis of Switched-Rigid Floating Oscillator - Prabhakar R. Marur (Shock and Vibration)
In explicit finite element simulations, a technique called deformable-to-rigid (D2R) switching is used routinely to reduce the computation time. Using the D2R option, the deformable parts in the model can be switched to rigid and reverted back to deformable when needed during the analysis. The time of activation of D2R however influences the overall dynamics of the system being analyzed. In this paper, a theoretical basis for the selection of time of rigid switching based on system energy is established. A floating oscillator problem is investigated for this purpose and closed-form analytical expressions are derived for different phases in rigid switching. The analytical expressions are validated by comparing the theoretical results with numerical computations.